Resin sheets for encapsulating hollow electronic components and hollow electronic components

JP2026169125APending Publication Date: 2026-10-16TOYO INK MFG CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2025178045
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2025-10-22
Publication Date
2026-10-16

AI Technical Summary

Benefits of technology

【0009】 本開示によれば、優れた柔軟性と、低熱膨張性との両立が可能な中空電子部品封止用樹脂シート、およびそれを用いた中空電子部品を提供できるという優れた効果を奏する。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026169125000001_ABST
    Figure 2026169125000001_ABST
Patent Text Reader

Abstract

This invention provides a resin sheet for encapsulating hollow electronic components that offers both excellent flexibility and low thermal expansion, and a hollow electronic component using the same. [Solution] A resin sheet for sealing hollow electronic components, for forming a sealing layer 4 of a hollow electronic component 10, wherein the resin sheet is a resin composition comprising a thermosetting resin (A), a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D). Because this resin sheet has excellent flexibility, it forms a sealing layer 4 on an unsealed electronic component 2 while maintaining the hollow structure 3. Furthermore, this resin sheet is lightweight, offers a high degree of design freedom, and can be integrated into complex shapes. In addition, because this resin sheet has low thermal expansion, it can prevent solder cracks from occurring when used in a hollow electronic component.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This disclosure relates to resin sheets for encapsulating hollow electronic components and hollow electronic components. [Background technology]

[0002] Hollow electronic components such as SAW filters, which allow only signals of specific frequencies to pass through and perform noise reduction, are equipped with a sealing layer to protect the electronic component from physical shock or temperature changes. This sealing layer is required to seal the electronic component while maintaining a hollow structure between the electronic component and the substrate. Many heat-meltable resin sheets have been developed as sealing layers that easily maintain a hollow structure and also offer excellent dimensional stability.

[0003] Patent Document 1 discloses a resin sheet for hollow sealing that contains 70 to 90% by volume of an inorganic filler and whose physical properties, such as the coefficient of linear expansion, are within a specific range. [Prior art documents] [Patent Documents]

[0004] [Patent Document 1] Japanese Patent Publication No. 2014-209568 [Overview of the project] [Problems that the invention aims to solve]

[0005] Resin sheets used to encapsulate hollow electronic components are required to have the flexibility to stretch in order to uniformly cover electronic components of various shapes with differences in height. Furthermore, from the viewpoint of preventing cracks in the solder that joins the substrate and the electronic components, it is desirable for resin sheets for encapsulating hollow electronic components to have low thermal expansion properties.

[0006] As mentioned above, flexibility and thermal expansion are usually in a trade-off relationship. The resin sheet described in Patent Document 1 has low thermal expansion, but because it contains a large amount of inorganic filler, its flexibility was sometimes insufficient.

[0007] This disclosure has been made in view of the above-mentioned problems, and its purpose is to provide a resin sheet for encapsulating hollow electronic components that can achieve both excellent flexibility and low thermal expansion, and a hollow electronic component using the same. [Means for solving the problem]

[0008] After diligent research by the present inventors, we have found that the problems of this disclosure can be solved in the following embodiments, and have completed this disclosure. [1] A resin sheet for sealing hollow electronic components, for forming a sealing layer for hollow electronic components, wherein the resin sheet is a resin composition comprising a thermosetting resin (A), a polyfunctional maleimide compound having two or more maleimide groups (B), a benzoxazine compound (C), and an epoxy resin (D). [2] The resin sheet for sealing hollow electronic components according to [1], wherein the total content of a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D) in the resin composition is 5 to 180 parts by mass per 100 parts by mass of thermosetting resin (A). [3] The resin composition further comprises an inorganic filler (E), wherein the inorganic filler (E) comprises silica particles, the resin sheet for sealing hollow electronic components according to [1] or [2]. [4] The resin sheet for sealing hollow electronic components according to [3], wherein the content of the inorganic filler (E) in the resin composition is 5 to 70% by mass. [5] A resin sheet for sealing hollow electronic components according to any one of [1] to [4], wherein the coefficient of linear expansion at 150 to 200°C of the cured product obtained by curing the resin sheet at 180°C for 2 hours is 3 to 750 ppm / K. [6] A resin sheet for sealing hollow electronic components according to any of [1] to [5], wherein the elongation at break at 100°C is 300 to 2000%. [7] A resin sheet for encapsulating hollow electronic components according to any one of [1] to [6], wherein the resin sheet is bonded to a polyimide substrate and cured at 180°C for 2 hours, and the adhesive strength of the cured product at 25°C is 0.6 to 40 N / cm. [8] A hollow electronic component comprising a substrate, an electronic component mounted on the substrate, and a sealing layer that seals the electronic component while maintaining a hollow structure between the substrate and the electronic component, wherein the sealing layer is formed from a cured product of a resin sheet for sealing hollow electronic components as described in any of [1] to [7]. [Effects of the Invention]

[0009] According to this disclosure, it is possible to provide a resin sheet for encapsulating hollow electronic components that can achieve both excellent flexibility and low thermal expansion, and hollow electronic components using the same, which is an excellent advantage. [Brief explanation of the drawing]

[0010] [Figure 1] This is a schematic cross-sectional view showing two examples of hollow electronic components according to this embodiment. [Figure 2] This is a schematic diagram of the test substrate for this embodiment. [Modes for carrying out the invention]

[0011] The following provides a detailed description of the resin sheet for encapsulating hollow electronic components and the hollow electronic components using the same related to this disclosure. Furthermore, other embodiments are also included in the scope of this disclosure, insofar as they are consistent with the intent of this disclosure. In this specification, numerical ranges specified using "~" include the numbers before and after "~" as the lower and upper limits, respectively. In numerical ranges described stepwise within this specification, the upper or lower limit of one numerical range may be replaced with the upper or lower limit of another numerical range described stepwise. Furthermore, in numerical ranges described within this specification, the upper or lower limit of that range may be replaced with the values ​​shown in the examples. Unless otherwise noted, each component in this specification may be used independently, alone, or in combination of two or more. The numerical values ​​described herein refer to the values ​​obtained by the methods described in the [Examples] section below.

[0012] 1. Resin sheet for encapsulating hollow electronic components The resin sheet for encapsulating hollow electronic components (hereinafter also referred to as "this resin sheet") disclosed herein is a sheet suitable for forming an encapsulation layer for encapsulating hollow electronic components (for encapsulating hollow electronic components). As shown in Figure 1(a), a hollow electronic component (hollow device) includes a substrate 1, an electronic component 2 mounted on the substrate 1, and an encapsulation layer 4 that encapsulates the electronic component 2 while maintaining the hollow structure 3 (hollow portion) between the substrate 1 and the electronic component 2. Therefore, in a hollow electronic component 10, electronic components 2 of various shapes with differences in height, etc., are uniformly covered by the encapsulation layer 4 while maintaining the hollow structure 3 between the substrate 1 and the electronic component 2. Thus, this resin sheet has the advantage of being able to encapsulate multiple electronic components 2 formed on a substrate 1, etc., all at once. Of course, this resin sheet may also be used to encapsulate a single electronic component (semiconductor element). Furthermore, as shown in Figure 1(b), the electronic component 2 may be secondary encapsulated by a second encapsulation layer 5 provided on the primary encapsulation layer (first encapsulation layer) 4. Thus, the hollow electronic component according to this disclosure may have a second sealing layer 5 formed on a sealing layer (first sealing layer) 4, and the electronic component may be sealed by a plurality of sealing layers. Figures 1(a) and (b) are schematic cross-sectional views showing two examples of the hollow electronic component 10 according to this embodiment. Reference numeral 6 indicates, for example, a lead-free solder ball that joins the substrate 1 and the electronic component 2.

[0013] This resin sheet is a resin composition comprising a thermosetting resin (A), a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D), and is converted into a sealing layer 4 which is a cured product when sealing the electronic component 2 while maintaining the hollow structure. This resin sheet may be a single layer or a multilayer. In the case of a multilayer, layers of the same and / or different resin compositions are laminated. Hereinafter, the thermosetting resin (A), the polyfunctional maleimide compound (B) having two or more maleimide groups, the benzoxazine compound (C), the epoxy resin (D), and the inorganic filler (E) described later are also referred to as components (A) to (E), respectively. The above-mentioned second sealing layer 5 may contain these components and may satisfy the configuration of the present resin sheet.

[0014] As described above, the present resin sheet is excellent in flexibility, and thus is suitably used for applications where the sealing layer 4 is formed on the unsealed electronic component 2 while maintaining the hollow structure 3. In addition, the present resin sheet is lightweight, has a high degree of design freedom, and can be integrated into a complex shape, so that it is suitably used for applications in which a plurality of sealed semiconductor chips are mounted on a substrate and collectively sealed. Furthermore, since the present resin sheet has low thermal expansibility, it can prevent the occurrence of solder cracks when formed into a hollow electronic component.

[0015] In the present specification, the electronic component 2 is incorporated into an electric circuit or an electronic device to control electric signals, and may include the following semiconductor elements. The semiconductor elements include power semiconductor elements such as IGBTs (Insulated Gate Bipolar Transistors), MOSFETs (Metal Oxide Semiconductor Field Effect Transistors), SAW filters (Surface Acoustic Wave Filters), bipolar transistors, and diodes; optical semiconductor elements such as light-emitting elements and light-receiving elements such as LEDs; and semiconductor integrated circuits formed on a semiconductor substrate such as a silicon substrate, and semiconductor chips obtained by singulating and taking out the semiconductor integrated circuits formed on the semiconductor substrate. This resin sheet enables weight reduction, integration of complex shapes, etc., has a high degree of design freedom, and exhibits favorable dielectric properties, and is therefore suitable for use in the field of information and communications. Electronic components such as semiconductor elements are usually formed or mounted on the upper surface of a base substrate.

[0016] In the present disclosure, "sealing" refers to forming a sealing layer 4 by coating an object (for example, the substrate 1 and the electronic component 2) using the present resin sheet while maintaining the hollow structure 3, followed by curing. The sealing layer 4 of the present disclosure includes all aspects in which the electronic component 2 is covered with the sealing layer 4, and in addition to the aspect of directly sealing the electronic component 2, also includes the aspect of further sealing a semiconductor module or the like in which the electronic component 2 is sealed. Among these, the present resin sheet is excellent in flexibility, has low thermal expansivity, and is also excellent in adhesive strength and heat resistance, and thus is particularly suitably applied to an aspect of collective sealing while preventing lifting and peeling from the substrate 1.

[0017] The linear expansion coefficient and adhesive strength of the present disclosure are defined under the conditions of a sufficiently cured stage for evaluating these properties, that is, under the conditions of subjecting the resin sheet to a curing (heating) treatment at 180°C for 2 hours. The above-mentioned "sufficiently cured stage" may include not only a cured product but also a product in the course of curing, not a cured product. As used herein, the term "cured product" refers to a state of being cured to such an extent that the curing reaction does not substantially proceed even with further heating, and the sealing layer is a (fully) cured product. A portion of the resin sheet may undergo a curing reaction during formation, but a state in which the resin sheet can be cured by further heating is not included in the (fully) cured product referred to herein. At the stage of the resin composition (thermosetting resin composition), it may be in a B-stage state in which a part of the components is semi-cured. The cured product of the resin composition is usually obtained by subjecting the resin composition to a heat treatment at 100 to 180°C for about 30 minutes to 5 hours. From the above, the present resin sheet may include those before full curing, more specifically, uncured ones and semi-cured ones. Further, the cured product of the present resin sheet means a product obtained by fully curing the present resin sheet.

[0018] The coefficient of linear expansion (CTE) at 150-200°C for the cured product obtained by curing the resin sheet at 180°C for 2 hours is preferably 3-750 ppm / K. If the coefficient of linear expansion is 3 ppm / K or higher, even if the package structure is subjected to high-temperature treatment after sealing, the difference in linear expansion between the resin sheet and the substrate or electronic components can be reduced, and warping of the substrate can be easily prevented. From a similar viewpoint, the coefficient of linear expansion is more preferably 5 ppm / K or higher, even more preferably 50 ppm / K or higher, and particularly preferably 120 ppm / K or higher. Furthermore, if the coefficient of linear expansion is 750 ppm / K or lower, solder crack resistance is even better. From a similar viewpoint, the coefficient of linear expansion is more preferably 500 ppm / K or lower, even more preferably 300 ppm / K or lower, and particularly preferably 200 ppm / K or lower. The method for measuring the coefficient of linear expansion will be described later. Furthermore, the coefficient of linear expansion can be adjusted by changing the types of components (B) to (E) in the resin composition or by adjusting the amounts added. More specifically, the rigid molecular structure of the polyfunctional maleimide compound (B), the structural stabilization by hydrogen bonding formed within the benzoxazine compound (C), the increase in crosslinking density by the epoxy resin (D), and the increased density of the inorganic filler (E) are thought to contribute to a decrease in the coefficient of linear expansion.

[0019] The elongation at break of the resin sheet (before curing) at 100°C is preferably 300 to 2000%. If the elongation at break is 300 to 2000%, the coverage of recesses formed by the mounting of electronic components will be better. More specifically, if the elongation at break is 300% or more, it is possible to maintain appropriate breaking strength while providing appropriate deformability, and significantly improve the occurrence of defects such as cracks and fractures in the sealing layer. From a similar viewpoint, the elongation at break is more preferably 500% or more, even more preferably 900% or more, and particularly preferably 1200% or more. Furthermore, if the elongation at break is 2000% or less, it is possible to easily prevent the resin sheet from entering hollow parts. From a similar viewpoint, the elongation at break is more preferably 1800% or less, even more preferably 1600% or less, and particularly preferably 1500% or less. Furthermore, if the resin sheet exhibits anisotropy in elongation, the direction with the lowest elongation should be 300% or more, and the direction with the highest elongation should be 2000% or less. The method for measuring this fracture elongation will be described later. Furthermore, the elongation at break can be adjusted by changing the types of components (A) to (E) in the resin composition or by adjusting the amounts added. More specifically, the introduction of a rigid skeleton such as a polyfunctional maleimide compound (B) or the incorporation of an inorganic filler (E) tends to increase the elasticity of the resin sheet and decrease the elongation at break. On the other hand, the addition of a thermoplastic resin or an epoxy resin with a low melting point (D) tends to soften the resin when heated and increase its flexibility. In addition, the benzoxazine compound (C) tends to increase the elongation at break by crosslinking with the curing agent or resin in the B stage and increasing its molecular weight.

[0020] The adhesive strength at 25°C of the cured product, which is formed by bonding the resin sheet to a polyimide substrate and curing (heating) it at 180°C for 2 hours, is preferably 0.6 to 40 N / cm. If the adhesive strength is 0.6 N / cm or higher, it is possible to easily prevent the resin sheet from lifting and peeling off from the adherend during thermal shock testing. From a similar viewpoint, the adhesive strength is more preferably 0.9 N / cm or higher, even more preferably 1.2 N / cm or higher, and particularly preferably 1.5 N / cm or higher. Furthermore, if the adhesive strength is 40 N / cm or lower, it is possible to easily re-peel off the resin sheet in the event of processing defects or failure analysis, facilitating reprocessing and recovery of parts. From a similar viewpoint, the adhesive strength is more preferably 25 N / cm or lower, even more preferably 15 N / cm or lower, and particularly preferably 10 N / cm or lower. The adhesive strength can be adjusted by controlling the amount of components (B) to (E) added to the resin composition and the film thickness of the resin sheet. More specifically, increasing the amount of polyfunctional maleimide compound (B), benzoxazine compound (C), and epoxy resin (D) tends to increase the crosslink density within the resin sheet, thereby increasing the adhesive strength. On the other hand, increasing the amount of inorganic filler (E) tends to impair the anchoring ability to the substrate, thereby decreasing the adhesive strength. Furthermore, reducing the film thickness of the resin sheet tends to increase the stress generated at the adhesive interface, thereby decreasing the adhesive strength.

[0021] The Tg of the resin sheet after heating at 180°C for 2 hours is preferably 20 to 200°C from the viewpoint of heat resistance. The lower limit of the Tg is more preferably 25°C, even more preferably 30°C, and particularly preferably 40°C. The upper limit of the Tg is more preferably 190°C, even more preferably 180°C, and particularly preferably 170°C. The Tg of the resin sheet can be adjusted by adjusting the amount of components (B) to (E) added to the resin composition. Specifically, increasing the amount of the polyfunctional maleimide compound (B), the benzoxazine compound (C), and the epoxy resin (D) increases the rigid molecular structure in the resin sheet and further increases the crosslinking density, thereby raising the Tg.

[0022] The thickness of the resin sheet can be appropriately designed within the range in which the effects of this disclosure can be obtained. For example, the thickness of the resin sheet can be 1 to 1000 μm. From the viewpoint of coverage and handling, 5 to 300 μm is preferable, and 10 to 100 μm is more preferable. By setting the thickness of the resin sheet to 1 μm or more, the pressure in the pressing process is diffused within the resin sheet, and sufficient coverage can be easily achieved. By setting the thickness of the resin sheet to 1000 μm or less, the degree of design freedom can be further increased. In addition, the pressure loss absorbed by the resin sheet in response to the pressure applied in the pressing process is small, and the resin (A), etc., flows sufficiently, so excellent coverage can be easily achieved.

[0023] Conventionally, encapsulants such as Encap have been used as the sealing layer 4, but this sometimes presented challenges in terms of productivity. Therefore, when using a coating type such as a resin sheet, that is, when the sealing layer 4 is coated along the shape of the electronic component 2, gaps tend to form between the adherend and the coating layer at the corners of the uneven surfaces formed by the mounting of the electronic component 2, especially at right angles. Furthermore, these gaps tend to form over time, which can lead to problems with storage stability.

[0024] However, with this resin sheet, a sealing layer 4 can be formed along various shapes of electronic components 2 with height differences in a single step, thus reducing material loss from the resin sheet. Furthermore, because it can be coated in one step, productivity and design flexibility can be significantly increased. Moreover, by including specific materials described later, this resin sheet significantly improves the gaps that occur at the corners (especially at right angles and other shapes) between the adherend (electronic component 2) and the coating layer, achieving excellent coating performance. After forming the sealing layer 4, other functional layers such as a conductive layer may be further coated, and since functional layers can be laminated using the same equipment, productivity is excellent.

[0025] This resin sheet may be used as a laminated sheet in which one or more functional sheets are laminated onto this resin sheet. The functional sheets are not particularly limited. Specifically, examples of functional sheets include electromagnetic wave shielding sheets, thermal conductive sheets for dissipating heat from semiconductor elements, shielding sheets for concealing or shielding semiconductor elements from light, moisture-proof sheets for protecting semiconductor elements from moisture, decorative sheets, flame-retardant sheets with flame retardancy, protective sheets with hard-coat properties, bonding sheets for improving adhesion to semiconductor elements, and any combination thereof. A functional layer can be formed by coating this resin sheet with a functional sheet.

[0026] Furthermore, as shown in Figure 1(b), a second sealing layer 5, for example, in the form of a tablet, liquid, granules, or a sheet, may be applied to the resin sheet (sealing layer 4) to provide secondary sealing for the substrate 1 and electronic components 2. As the second sealing layer 5, a sealing material consisting of, for example, a conventionally known epoxy resin, curing agent, inorganic filler, curing catalyst, coupling agent, flame retardant, coloring agent, etc., can be used as appropriate. Also, as described above, the second sealing layer 5 may satisfy the composition of the resin sheet.

[0027] This resin sheet can be manufactured using conventionally known methods; however, please refer to the examples described below for details.

[0028] 1-1.Resin composition This resin sheet is a resin composition (hereinafter also referred to as "this composition") comprising a thermosetting resin (A), a polyfunctional maleimide compound having two or more maleimide groups (B), a benzoxazine compound (C), and an epoxy resin (D). It is preferable that these components in the resin composition harden with each other by heat treatment. In addition, a portion of the resin composition may be hardened at the stage of this resin sheet.

[0029] 1-1a.Thermosetting resin (A) The thermosetting resin (A) has the function of adhering to and fixing the adherend as a binder. The thermosetting resin (A) may contain other materials such as thermoplastic resins and photocurable resins, or it may consist solely of thermosetting resin, as long as it has thermosetting properties as a whole. The thermosetting resin is a resin that has multiple functional groups that can be used in crosslinking reactions by heating, and may also have self-crosslinkable functional groups.

[0030] The functional groups of the thermosetting resin can be appropriately selected in combination with other components described later, and examples include hydroxyl groups, carboxyl groups, amino groups, epoxy groups, oxetanyl groups, oxazoline groups, oxazine groups, aziridine groups, thiol groups, isocyanate groups, blocked isocyanate groups, and silanol groups. From the viewpoint of reactivity, carboxyl groups, hydroxyl groups, and epoxy groups are preferred among the functional groups.

[0031] The acid value of the thermosetting resin is preferably 1 to 30 mgKOH / g, more preferably 2 to 20 mgKOH / g, and even more preferably 3 to 15 mgKOH / g. By setting the acid value of the thermosetting resin to 1 mgKOH / g or higher, the intermolecular forces with the adherend, such as electronic components, are maintained well while optimizing the crosslinking density with other components, thereby further improving sealing performance. Furthermore, by setting the acid value of the thermosetting resin to 30 mgKOH / g or lower, adhesion can be further improved while maintaining good intermolecular forces with the adherend, such as electronic components.

[0032] The content of thermosetting resin (A) in this resin sheet (solid content) is preferably 20 to 50% by mass. Examples of thermosetting resin (A) include amide resins, imide resins, (meth)acrylic resins, maleic acid resins, butadiene resins, urethane resins such as urethane resins and urethane urea resins, oxetane resins, phenoxy resins, polyamide-imide resins, alkyd resins, amino resins, polylactic acid resins, oxazoline resins, benzoxazine resins, silicone resins, and fluororesins. Among these, it is preferable that the thermosetting resin (A) contains a urethane resin including urethane resin and / or urethane urea resin. Conventional known resins can be used as appropriate, and commercially available products may be used, for example.

[0033] The weight-average molecular weight (Mw) of the thermosetting resin (A) can be designed as appropriate, but from the viewpoint of increasing the mechanical strength of the sealing layer and improving the storage stability of the resin sheet, 10,000 to 1,000,000 is preferred. From the viewpoint of durability and adhesion, 25,000 to 300,000 is more preferred, and 50,000 to 200,000 is even more preferred. The ratio of the number-average molecular weight (Mn) to Mw (Mw / Mn), which indicates the degree of dispersion of the thermosetting resin (A), is preferably 1.0 to 17, more preferably 1.5 to 14, and even more preferably 2.0 to 10. Setting Mw / Mn to 1.0 to 17 makes it easier to control the fluidity of the resin and further improves the coating performance. In addition, the rate of wetting of the adherend is made more uniform, so the adhesion is further improved.

[0034] The urethane resin can be designed as appropriate and is not limited, but a preferred urethane resin (A1) is one that contains structural units derived from at least one polyol, dimerol, and trimertriol, and / or structural units derived from at least one polyamine, dimeramine, and trimertriamine, and has urethane bonds, and may also have urea bonds. Hereinafter, the structures derived from the above structural units will be collectively referred to as "dimer structures". Urethane bonds are formed by the reaction of a hydroxyl group and an isocyanate group, and urea bonds are formed by the reaction of an amino group and an isocyanate group. The urethane resin is obtained by urethane bonding a reaction component containing two or more polyol components and a polyisocyanate component having two or more isocyanate groups in one molecule. For example, the urethane urea resin can be obtained by reacting a urethane prepolymer of a terminal isocyanate obtained by reacting a polyol and a polyisocyanate with a chain extender such as a polyamine component having two or more amino groups in one molecule.

[0035] By using a dimer structure and a urethane-based resin (A1) that combines urethane bonds or urethane bonds and urea bonds, excellent flexibility and appropriate elongation at break of the resin sheet are achieved, resulting in superior sealing performance. Furthermore, the lone pairs of electrons of nitrogen atoms contained in the urethane bonds prevent tearing and breakage of the sealing layer, enabling not only excellent coating performance but also strong adhesion to the adherend.

[0036] 1-1b. Polyfunctional maleimide compounds (B) A polyfunctional maleimide compound (B) is a compound having two or more maleimide groups and can be represented by the following general formula (1). [ka] In formula (1), R 1 is a k-valent organic group, and R 2 , R 3 This is a hydrogen atom or a monovalent organic group. The organic group may be a hydrocarbon group composed only of C and H, or it may be a group that includes heteroatoms such as N, O, and S, or halogen atoms, in addition to C and H. k is an integer greater than or equal to 2, preferably an integer between 2 and 10. R 2 ,R 3 These may be the same group or different groups.

[0037] In formula (1), R 1 Examples of alkylene groups include alkylene groups and arylene groups. Alkylene groups include those with 1 to 20 carbon atoms. Alkylene groups include linear alkylene groups and cyclic alkylene groups. Linear alkylene groups may be linear or branched. Examples of linear alkylene groups include methylene groups, ethylene groups, and hexamethylene groups. Arylene groups include those with 1 to 20 carbon atoms. Examples of arylene groups include phenylene groups and methylphenylene groups.

[0038] In formula (1), R 2 , R 3 Examples of organic groups include alkyl or aryl groups having 1 to 20 carbon atoms. Alkyl groups include methyl, ethyl, and propyl groups. Aryl groups include phenyl, substituted phenyl, naphthyl, and substituted naphthyl groups.

[0039] Examples of such polyfunctional maleimide compounds include N,N'-ethylenebismaleimide, N,N'-hexamethylenebismaleimide, N,N'-(1,3-phenylene)bismaleimide, N,N'-[1,3-(2-methylphenylene)]bismaleimide, N,N'-(1,4-phenylene)bismaleimide, bis(4-maleimidephenyl)methane, bis(3-methyl-4-maleimidephenyl)methane, bis(4-male (imidophenyl) ether, bis(4-maleimidophenyl sulfone), bis(4-maleimidophenyl) sulfide, bis(4-maleimidophenyl) ketone, bis(4-maleimidocyclohexyl) methane, 1,4-bis(4-maleimidophenyl) cyclohexane, 1,4-bis(4-maleimidomethyl) cyclohexane, 1,4-bis(maleimidomethyl)benzene, 1,3-bis(3-maleimidophenoxy)benzene, Bis[4-(4-maleimidophenoxy)phenyl]methane, 1,1-bis[4-(3-maleimidophenoxy)phenyl]ethane, 1,1-bis[4-(4-maleimidophenoxy)phenyl]ethane, 1,2-bis[4-(3-maleimidophenoxy)phenyl]ethane, 1,2-bis[4-(4-maleimidophenoxy)phenyl]ethane, 2,2-bis[4-(4-maleimidophenoxy)phenyl]propane, 2,2 -Bis[4-(3-maleimidophenoxy)phenyl]butane, 2,2-bis[4-(3-maleimidophenoxy)phenyl]butane, 2,2-bis[4-(3-maleimidophenoxy)phenyl]-1,1,1,3,3,3-hexafluoropropane, 2,2-bis[4-(4-maleimidophenoxy)phenyl]1,1,1,3,3,3-hexafluoropropane, 4,4'-bis(3-maleimidophenoxy)biphenyl, 4,4'-Bis(4-maleimidophenoxy)biphenyl, bis[4-(3-maleimidophenoxy)phenyl]ketone, bis[4-(4-maleimidophenoxy)phenyl]ketone, bis[4-(3-maleimidophenoxy)phenyl]sulfide, bis[4-(4-maleimidophenoxy)phenyl]sulfide, bis[4-(3-maleimidophenoxy)phenyl]sulfoxide, bis[4-(4-(maleimidophenoxy)phenyl]sulfoxide, bis[4-(3-maleimidophenoxy)phenyl]sulfone, bis[4-(4-maleimidophenoxy)phenyl]sulfone, bis[4-(3-maleimidophenoxy)phenyl]ether, bis[4-(4-maleimidophenoxy)phenyl]ether, 1,4-bis[4-(4-maleimidophenoxy)-α,α-dimethicone Examples include 1,3-bis[4-(4-maleimidophenoxy)-α,α-dimethylbenzene]benzene, 1,4-bis[4-(3-maleimidophenoxy)α,α-dimethylbenzene]benzene, 1,3-bis[4-(3-maleimidophenoxy)-α,α-dimethylbenzene]benzene, 1,4-bis[4-(4-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene, 1,3-bis[4(4-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene, 1,4-bis[4-(3-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene, and 1,3-bis[4-(3-maleimidophenoxy)-3,5-dimethyl-α,α-dimethylbenzene]benzene.

[0040] Furthermore, the polyfunctional maleimide compound (B) can include not only the nonpolymers described above, but also polymers represented by the following general formulas (2) and (3).

[0041] [ka] [ka]

[0042] In formulas (2) and (3), n and m represent the number of repeating units, with an average value of 0 to 10. In formulas (2) and (3), the methylene group is a group bonded to the 2nd or 3rd position of the aromatic ring, and R is a substituent bonded one or more times to any position where a methylene group is not bonded. Examples of R include alkyl groups and aryl groups having 1 to 20 carbon atoms.

[0043] The content of the polyfunctional maleimide compound (B) in this composition is preferably 5 to 80 parts by mass per 100 parts by mass of the thermosetting resin (A). If the content of the polyfunctional maleimide compound (B) is 5 parts by mass or more, the solder crack resistance and heat resistance are further improved. From a similar viewpoint, the content of the polyfunctional maleimide compound (B) is more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more. Furthermore, if the content of the polyfunctional maleimide compound (B) is 80 parts by mass or less, the adhesion is further improved. From a similar viewpoint, the content of the polyfunctional maleimide compound (B) is more preferably 60 parts by mass or less, and even more preferably 40 parts by mass or less.

[0044] 1-1c. Benzooxazine compounds (C) Benzooxazine compound (C) is a compound having a benzooxazine ring in its molecule. While there are no particular limitations to benzooxazine compound (C), compounds having two or more benzooxazine rings in one molecule are preferred from the viewpoint of crosslinkability and curability. Specific examples of benzooxazine compounds include Fa-type benzooxazine compounds obtained by the reaction of a bisphenol compound, an amine compound (e.g., aniline), and formaldehyde, such as bisphenol A-type benzooxazine compounds and bisphenol F-type benzooxazine compounds, and Pd-type benzooxazine compounds obtained by the reaction of a phenyldiamine compound, a phenol compound, and formaldehyde, such as diaminodiphenylmethane-type benzooxazine compounds. These can be commercially available products. Furthermore, these are nonpolymers. Between Fa-type benzoxazine compounds and Pd-type benzoxazine compounds, Pd-type benzoxazine compounds are preferred from the viewpoint of superior heat resistance, among other advantages.

[0045] For example, a bisphenol F-type benzoxazine compound, which is a Fa-type benzoxazine compound, has the structure shown in formula (4) below. This is obtained by the reaction of bisphenol F, aniline, and formaldehyde. [ka]

[0046] For example, Pd-type benzoxazine compounds have a structure like that shown in formula (5) below. This is obtained by the reaction of 4,4'-methylenedianiline with phenol and formaldehyde. [ka]

[0047] The content of the benzoxazine compound (C) in this composition is preferably 1 to 50 parts by mass per 100 parts by mass of the thermosetting resin (A). If the content of the benzoxazine compound (C) is 1 part by mass or more, the flame retardancy can be further improved. From a similar viewpoint, the content of the benzoxazine compound (C) is more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more. Furthermore, if the content of the benzoxazine compound (C) is 50 parts by mass or less, the brittleness of the sheet can be mitigated, and the conformability to electronic components can be easily improved. From a similar viewpoint, the content of the benzoxazine compound (C) is more preferably 45 parts by mass or less, and even more preferably 40 parts by mass or less.

[0048] 1-1d. Epoxy resin (D) The epoxy resin (D) is not particularly limited and can be any resin having epoxy groups in its molecule. For improving the heat resistance and adhesion of the coating film, a polyfunctional epoxy resin with three or more functions is useful, while for applications requiring flexibility in the coating film, a bifunctional epoxy resin such as bisphenol A type and bisphenol F type, described later, is useful. The epoxy resin (D) may consist solely of a trifunctional epoxy resin, or it may be a combination of a trifunctional epoxy resin and a bifunctional or monofunctional epoxy resin.

[0049] Examples of epoxy resins (D) include bisphenol-type epoxy resins, triphenylmethane-type epoxy resins, novolac-type epoxy resins, alicyclic epoxy resins, glycidyl esters, glycidylamines, heterocyclic epoxy resins, and brominated epoxy resins.

[0050] Examples of bisphenol-type epoxy resins include bisphenol A type epoxy resin, bisphenol F type epoxy resin, and bisphenol S type epoxy resin. Examples of phenylmethane-type epoxy resins include diphenylmethane-type epoxy resins and triphenylmethane-type epoxy resins. Examples of novolac-type epoxy resins include phenol novolac-type epoxy resins, cresol novolac-type epoxy resins, bisphenol A novolac-type epoxy resins, and dicyclopentadiene novolac-type epoxy resins. Examples of alicyclic epoxy resins include 3,4-epoxy-6-methylcyclohexylmethyl-3,4-epoxy-6-methylcyclohexanecarboxylate, 3,4-epoxycyclohexylmethyl-3,4-epoxycyclohexanecarboxylate, and 1-epoxyethyl-3,4-epoxycyclohexane. Examples of glycidyl esters include diglycidyl phthalate, diglycidyl tetrahydrophthalate, and glycidyl dimer acid. Examples of glycidylamines include tetraglycidyldiaminodiphenylmethane, triglycidyl-P-aminophenol, and N,N-diglycidylaniline. Examples of heterocyclic epoxy resins include 1,3-diglycidyl-5,5-dimethylhydantoin and triglycidyl isocyanurate. Examples of brominated epoxy resins include tetrabromobisphenol A type epoxy resin, tetrabromobisphenol F type epoxy resin, brominated cresol novolac type epoxy resin, and brominated phenol novolac type epoxy resin.

[0051] The content of the epoxy resin (D) in this composition is preferably 1 to 50 parts by mass per 100 parts by mass of the thermosetting resin (A). If the content of epoxy resin (D) is 1 part by mass or more, the adhesive properties are even better. From a similar viewpoint, the content of epoxy resin (D) is more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more. Furthermore, if the content of epoxy resin (D) is 50 parts by mass or less, the protective properties of electronic components are even better. From a similar viewpoint, the content of epoxy resin (D) is more preferably 45 parts by mass or less, and even more preferably 40 parts by mass or less.

[0052] The total content of the polyfunctional maleimide compound (B), benzoxazine compound (C), and epoxy resin (D) in this composition is preferably 5 to 180 parts by mass per 100 parts by mass of the thermosetting resin (A). If the total content of these components is 5 parts by mass or more, the solder crack resistance and adhesion are further improved. From a similar viewpoint, the total content of these components is more preferably 10 parts by mass or more, even more preferably 20 parts by mass or more, and particularly preferably 60 parts by mass or more. Furthermore, if the total content of these components is 180 parts by mass or less, the penetration of the resin sheet into the hollow portion can be easily suppressed, and the adhesion is further improved. From a similar viewpoint, the total content of these components is more preferably 160 parts by mass or less, even more preferably 140 parts by mass or less, particularly preferably 120 parts by mass or less, and most preferably 100 parts by mass or less.

[0053] Furthermore, the components (B) to (D) mentioned above can be mixed with other components (for example, thermosetting resin (A)) in a pre-mixed state. In addition, heat (for example, 100°C or higher) can be applied to melt and mix them.

[0054] 1-1e. Other ingredients • Inorganic filler (E) This composition may contain an inorganic filler (E) such as a metal oxide. Examples of inorganic fillers (E) include silica, alumina, magnesium hydroxide, barium sulfate, calcium carbonate, titanium dioxide, zinc oxide, antimony trioxide, magnesium oxide, talc, kaolinite, mica, magnesium carbonate base, sericite, montmololinite, bentonite, boron nitride, aluminum nitride, titanium nitride, and carbon black. Among these, titanium dioxide, titanium nitride, silica, talc, mica, kaolinite, or montmorillonite are preferred from the viewpoint of coating film resistance to scratches, titanium dioxide, titanium nitride, and silica are more preferred, and silica is particularly preferred. In this composition, it is preferable that the silica is in particulate form and contains silica particles. In this disclosure, from the viewpoint of coating film resistance, two or more inorganic fillers may be included.

[0055] The average primary particle size (hereinafter referred to as particle size) of the inorganic filler (E) is preferably 0.1 to 50 μm. A particle size of 0.1 μm or more makes it easier to maintain the viscosity of the resin composition at a level suitable for coating. Furthermore, a particle size of 50 μm or less further improves the smoothness of the coating film. The particle size of the inorganic filler (E) can be determined from the average value of about 20 primary particles observed in an image magnified to approximately 50,000 to 1,000,000 times using a transmission electron microscope (TEM).

[0056] The inorganic filler (E) may be mechanically crushed and then mixed with a thermosetting resin (A), and the mixture may be further dispersed. The use of a dispersant is preferable for the dispersion process. The dispersant can impart repulsive forces between the inorganic fillers so that the inorganic fillers dispersed after the aforementioned dispersion process do not re-aggregate. Conventional known compounds can be used as dispersants. Examples include polymeric dispersants, pigment derivative dispersants, or surfactants selected from cationic, anionic, or nonionic types. The Mw of these dispersants is, for example, around 1,000 to 30,000.

[0057] The inorganic filler (E) content in this composition (solids) is preferably 5 to 70% by mass. If the inorganic filler (E) content is 5% by mass or more, the entry of the resin sheet into the hollow portion can be easily prevented, and furthermore, solder crack resistance is improved. From a similar viewpoint, the inorganic filler (E) content is more preferably 10% by mass or more. Furthermore, if the inorganic filler (E) content is 70% by mass or less, adhesion and solder crack resistance are improved. From a similar viewpoint, the inorganic filler (E) content is more preferably 60% by mass or less.

[0058] This composition may contain a curing accelerator to adjust the crosslinking rate during the curing process or the physical properties of the resin sheet. The curing accelerator is not particularly limited and can be selected as appropriate. Specific examples of curing accelerators include amine-based curing accelerators, guanidine-based curing accelerators, and metal-based curing accelerators. These may be used individually or in combination of two or more. From the viewpoint of coating suitability, the content of the curing accelerator is preferably 0.01 to 10% by mass, and more preferably 0.1 to 5% by mass, in the composition (solid content).

[0059] This composition may be further modified with various additives, without departing from the spirit of this disclosure. For example, thermally conductive fillers can be used. Furthermore, additives such as antistatic agents, flame retardants, antioxidants, UV inhibitors, colorants, dispersants, surface conditioning additives, curing retarders, softeners, blocking inhibitors, adhesion improvers, and embedding improvers may be added as appropriate.

[0060] 2. Hollow electronic components The hollow electronic component 10 of this disclosure (hereinafter also referred to as "this hollow electronic component") includes, as shown in Figure 1(a), a substrate 1, an electronic component 2 mounted on the substrate 1, and a sealing layer 4 that seals the electronic component 2 while maintaining the hollow structure 3 between the substrate 1 and the electronic component 2. In this hollow electronic component, the sealing layer 4 is formed from a cured product of the resin sheet for sealing hollow electronic components of this disclosure described above. The manufacturing method for this hollow electronic component is not particularly limited, and conventionally known methods can be applied. However, by using this resin sheet, multiple electronic components 2, such as semiconductor elements, mounted on a substrate 1 can be covered all at once while maintaining the hollow structure 3. Specifically, the resin sheet is temporarily attached to the multiple electronic components 2, and the resin sheet is softened by heating and / or pressurizing it to cover and bond the top surface of the substrate 1 and the top and side surfaces of the multiple electronic components 2 while maintaining the hollow structure 3. Then, by curing the resin sheet, a sealing layer 4 is formed that encapsulates the electronic components 2, and the hollow electronic component can be obtained. In this case, the resin sheet may be a single layer or multiple layers of the resin sheet of this disclosure used alone. Also, as shown in Figure 1(b), the hollow electronic component may have a second sealing layer 5, for example, in the form of a tablet, liquid, granules, or a sheet, covering a sealing layer (first sealing layer) 4 made of a cured product of the resin sheet, thereby secondary sealing the substrate 1 and the electronic component 2. Thus, in the hollow electronic component, the electronic component 2 may be sealed by multiple sealing layers. [Examples]

[0061] The present disclosure will be described in detail below with reference to examples and comparative examples, but the present disclosure is not limited to the examples. In the following description, "parts" and "%" refer to "parts by mass" and "% by mass," respectively, unless otherwise specified.

[0062] 1. Resin sheets for encapsulating hollow electronic components (hereinafter referred to as "resin sheets") The raw materials used in each example are listed below.

[0063] 1-1.Thermosetting resin (A) [Synthesis of thermosetting resin a1] [Synthesis of polyester diols] In a glass flask equipped with a stirrer, thermometer, reflux condenser, nitrogen inlet tube, and vacuum equipment, 266 parts terephthalic acid, 30 parts adipic acid, 212 parts 3-methyl-1,5-pentanediol, and 25 parts ethylene glycol were charged and stirred while passing nitrogen gas through. The mixture was gradually heated under atmospheric pressure and reacted at 200-230°C for approximately 8 hours to obtain a liquid with an acid value of 43 mg KOH / g. Next, 0.01 parts tetra-n-butoxytitanium was charged, and after purging with nitrogen, the mixture was stirred at 180°C for 30 minutes under a sealed condition. Then, the mixture was reacted at 230°C and 5 mmHg for 2 hours to obtain a polyester diol with an acid value of 1.1 mg KOH / g, a hydroxyl value of 114.2 mg KOH / g, and a molecular weight of 982. The acid value and hydroxyl value were determined by weighing the thermosetting resin and measuring them using the potentiometric titration method of JIS K0070 with an automatic titrator GT-200 (product name) manufactured by Mitsubishi Chemical Analytical Corporation, and then converting them to solid content.

[0064] [Synthesis of urethane prepolymers] Next, 734 parts of the polyester diol, 23.9 parts of dimethylolpropionic acid, 219 parts of toluene diisocyanate, and 242 parts of toluene were charged into a reaction vessel equipped with a stirrer, thermometer, reflux condenser, dropping device, and nitrogen inlet tube, and the mixture was reacted at 50°C under a nitrogen atmosphere for 8 hours. To this, 1200 parts of toluene was added to obtain a urethane prepolymer solution having isocyanate groups at the ends.

[0065] [Synthesis of urethane polymers] Next, the obtained urethane prepolymer solution was heated to 70°C, and while maintaining this temperature, a solution of 20.0 parts 1,3-diaminopropane, 600 parts 2-propanol, and 961 parts toluene was added dropwise over 1 hour. After the dropwise addition was complete, the reaction was continued at 70°C for a further 6 hours to obtain a polyurethane resin (thermosetting resin a1) with a molecular weight (Mw) of 130,000, an acid value of 10 mgKOH / g, a Tg of 20°C, and a solids content of 25%.

[0066] 1-2. Maleimide complex compounds (mixture of components (B) to (D)) [Preparation of maleimide complex compounds m1-m4] The following compounds were prepared as maleimide composite compounds containing a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D). Maleimide complex compound m1: "HR3053 (product name)", manufactured by Printec Co., Ltd. Maleimide complex compound m2: "HR-YSP (product name)", manufactured by Printec Co., Ltd. Maleimide complex compound m3: "HR3070 (product name)", manufactured by Printec Co., Ltd. Maleimide complex compound m4: "HR3072 (product name)", manufactured by Printec Co., Ltd.

[0067] 1-3. Epoxy resin (D) [Prepare epoxy resins d1-d3] The following compounds were prepared as epoxy resins. Epoxy resin d1:3 functional epoxy compound "VG3101L (product name)", epoxy equivalent 210g / eq, manufactured by Printec Co., Ltd. Epoxy resin d2:2 functional epoxy compound "EPICLON 840 (product name)", epoxy equivalent 190 g / eq, contains hydroxyl groups, manufactured by DIC Corporation. Epoxy resin d3: Novolac-type epoxy compound "MEH-7851-SS (product name)", epoxy equivalent 105 g / eq, manufactured by Nippon Kayaku Co., Ltd.

[0068] 1-4. Additives The following compounds were prepared as additives. Additive f1: Carbodiimide compound "Carbodilite v-01 (product name)", epoxy equivalent 105 g / eq, manufactured by Nisshinbo Chemical Co., Ltd. Additive f2: Imidazole compound "Curesol 2E4MZ (product name)", manufactured by Shikoku Chemicals Co., Ltd. Additive f3: Silane coupling material "KBM403 (product name)", manufactured by Shin-Etsu Chemical Co., Ltd.

[0069] 1-5. Inorganic fillers (E) [Preparation of inorganic fillers e1 and e2] The following compounds were prepared as inorganic fillers. Inorganic filler e1: "Hi-Presilica TSN3N (trade name)", D 50 =2.0 μm, manufactured by Ube Exsymo Co., Ltd. Inorganic filler e2: "Mitsubishi Carbon Black MA-8 (trade name)", D 50 =24 nm, manufactured by Mitsubishi Chemical Corporation

[0070] 2. Measurement methods 2-1. Elongation at break The resin sheets with release film of each Example and Comparative Example obtained by the method described later were cut into a size of 20 mm in width × 60 mm in length. Next, the release film was peeled off to obtain a measurement sample (electronic component coating sheet). The measurement sample was placed under a temperature of 100°C (in air, 50% RH), and 1 minute later, a tensile test was performed at the same temperature with a tensile speed of 50 mm / min using a small desktop tester EZ-TEST (trade name, manufactured by Shimadzu Corporation) at an effective tensile size of 20 × 17 mm, to determine the elongation at break (%).

[0071] 2-2. Coefficient of linear thermal expansion (CTE) The resin sheets with release film of each Example and Comparative Example were cured at 180°C for 2 hours, and the release film was peeled off. The sheet was cut into a size of 4 mm in width × 20 mm in length, and the displacement was measured when a heating load was applied under the conditions of a load of 1 g, a temperature range from 0°C to 300°C, and a heating rate of 6°C / min using TMA Q400 manufactured by TA Instruments. The coefficient of linear thermal expansion was determined by the average of the slopes between 150°C and 200°C when plotted with the sample temperature on the horizontal axis and the displacement on the vertical axis.

[0072] 2-3. Adhesive strength The resin sheets with release films obtained from each example and comparative example using the method described later were cut to a size of 90 mm x 90 mm. Two sheets of polyimide film (Toray DuPont Co., Ltd.'s "Kapton 200EN (product name)") with a thickness of 50 μm and the same size were also prepared. The release films were peeled off the electronic component coating sheets of each example, and the polyimide films were sequentially applied to both sides of the electronic component coating sheets under the conditions of 90°C, 0.3 MPa, and 1 m / min. After that, they were hot-pressed under the conditions of 100°C, 1.0 MPa, and 3 min, and then cured at 180°C for 2 hours. Test pieces with a width of 10 mm and a length of 90 mm were cut from the cured samples, and a 90-degree peel test was performed using a small benchtop test machine EZ-TEST (product name, manufactured by Shimadzu Corporation) at a tensile speed of 50 mm / min in an environment of 25°C and 50% RH, and the adhesive strength A (N / cm) was measured.

[0073] 2-4. Glass transition temperature Tg The Tg of each example and comparative example sample (electronic component coating sheet) was measured using a dynamic viscoelasticity analyzer DVA-200 (product name, manufactured by IT Measurement Control Co., Ltd.) in accordance with JIS K7198. For the measurement, the resin sheet with release film for each example was cured at 180°C for 2 hours, then cut into 0.5cm x 3cm pieces, and the release film was removed. The deformation mode was tensile, with a strain of 0.08%, a frequency of 10Hz, a heating rate of 10°C / min, and the temperature at which the main dispersion peak of the loss tangent (tanδ) appeared in the temperature range of -50°C to 300°C was defined as Tg. In the case of a multi-layered coating sheet, there may be multiple maximum values ​​of the loss tangent (tanδ); in such cases, the highest temperature was used as the Tg (°C) of the sample.

[0074] 3. Preparation of resin sheets [Example 1] 100 parts of thermosetting resin a1 (solids), 3 parts of maleimide composite compound m1 (HR3053), 0.8 parts of additive f1 (Carbodilite V-01), 0.1 parts of additive f2 (2E4MZ), and 45 parts (30% by mass) of inorganic filler e1 and 0.8 parts (0.5% by mass) of inorganic filler e2 were placed in a container. Toluene was then added to the container to achieve a non-volatile content concentration of 33% by mass, and the mixture was stirred with a disperser for 10 minutes to obtain the composition. This composition was coated onto a release film (release-treated polyethylene terephthalate film, 50 μm thick) using a doctor blade to achieve a dry thickness of 20 μm. Next, a single-layer (first layer) resin sheet with a release film was obtained by drying at 100°C for 2 minutes.

[0075] [Examples 2-24, Comparative Examples 1 and 2] Except for changing the composition as shown in Tables 1 and 2, release film-coated resin sheets for Examples 2 to 24 and Comparative Examples 1 and 2 were obtained in the same manner as in Example 1.

[0076] Tables 1 and 2 below show the formulations of each example and comparative example. [Table 1] [Table 2]

[0077] 4. Preparation of the test SAW chip mounted substrate (hereinafter referred to as "test substrate 20") As substrate 11, a test substrate 20 was prepared by mounting five SAW chips (length 1.2 mm, width 1.2 mm, height 0.2 mm (200 μm)) as electronic components 12 on an FR-4 substrate (length 80 mm, width 80 mm, height 0.25 mm) made of glass epoxy, in rows of five with a mounting interval of 0.2 mm (200 μm). Lead-free solder balls 13 (height 50 μm) were used to bond the SAW chips to the FR-4 substrate. The solder balls 13 were placed 0.1 mm inward from the edges of the four corners of the SAW chips, and the SAW chips were bonded to the FR-4 substrate under bonding conditions of 200°C (see Figure 2). Figure 2 is a schematic diagram of the test substrate of this embodiment, with Figure 2(a) being a top view (plan view) and Figure 2(b) being a front cross-sectional view.

[0078] 5. Rating The resin sheets with release films for each example and comparative example were placed so that the resin sheet side of the release film-attached resin sheet was placed on the test substrate, and then heat-pressed under the conditions of 100°C, 0.1 MPa, and 1 min. After that, the release film was peeled off, and then heat-pressed again under the conditions of 100°C, 0.5 MPa, and 3 min. The substrates were heated at 180°C for 2 hours to obtain test substrates covered with resin sheets (test substrates with resin sheets). The obtained test substrates with resin sheets were evaluated as follows.

[0079] 5-1. SAW chip protection A cross-section was formed by polishing a test substrate with a resin sheet attached, allowing observation of the resin sheet's coverage of the SAW chip and its penetration into the hollow portion of the SAW. Ten arbitrary SAW chips were observed with an electron microscope (400x magnification), and the protectiveness of the SAW chips was judged according to the following criteria.

[0080] 5-1-1. SAW tip coating properties The condition of the resin sheet covering the SAW chips was observed, and the number of SAW chips that were completely covered by the resin sheet was counted and evaluated according to the following criteria. • Evaluation criteria A: There are 10 SAW chips covered with a resin sheet. B: The number of SAW chips covered with a resin sheet is 8 to 9. C: The number of SAW chips covered with a resin sheet is 6 to 7. D: The number of SAW chips covered with a resin sheet is 4 to 5. E: The number of SAW chips covered with a resin sheet is 3 or less. Not practical.

[0081] 5-1-2.SAW hollow part penetrability The penetration of the resin sheet into the hollow portion of the SAW chip was observed, and the number of SAW chips in which the solder ball at the bottom of the SAW chip was in contact with the resin sheet was counted and evaluated according to the following criteria. • Evaluation criteria A: The number of SAW chips in contact with the solder balls on the resin sheet is 0. B: The number of SAW chips in contact with the solder balls on the resin sheet is 1 to 2. C: The number of SAW chips in contact with the solder balls on the resin sheet is 3 to 4. D: The number of SAW chips in contact with the solder balls on the resin sheet is 5 to 6. E: The number of SAW chips in contact with the solder balls on the resin sheet is 7 or more. Not practical.

[0082] 5-2. Solder crack resistance after thermal shock testing Test substrates with resin sheets were placed in a thermal shock chamber TSA-43EL (product name, manufactured by ESPEC), and thermal shock tests were performed for 10 minutes at each temperature for 1000 cycles from -50°C to 125°C. After the test, the test substrates with resin sheets were polished to form a cross-section, allowing observation of the condition of the solder balls at the bottom of the SAW chips. Ten arbitrary SAW chips were observed with an electron microscope (magnification 400x), and cracks occurring in the solder balls at the bottom of the SAW chips were judged according to the following criteria. • Evaluation criteria A: The number of SAW chips with cracks in the solder balls is 0. B: The number of SAW chips with cracks in the solder ball is 1 to 2. C: There are 3 to 4 SAW chips with cracks in the solder balls. D: There are 5 to 6 SAW chips with cracks in the solder balls. E: There are 7 or more SAW chips with cracks in the solder balls. Not suitable for practical use.

[0083] 5-3. Adhesion after thermal shock testing A test substrate with a resin sheet was placed in a thermal shock chamber TSA-43EL (product name, manufactured by ESPEC), and a thermal shock test was performed for 10 minutes at each temperature for 1000 cycles from -50°C to 125°C. After the test, the test substrate with the resin sheet was polished to form a cross-section so that the under-bonding state between the resin sheet and the SAW chip could be observed. Ten arbitrary SAW chips were observed with an electron microscope (magnification 400x), and the state of delamination between the resin sheet and the SAW chip was judged according to the following criteria. • Evaluation criteria A: The number of SAW chips experiencing resin sheet delamination is 0. B: The number of SAW chips where delamination of the resin sheet has occurred is 1 to 2. C: There are 3 to 4 SAW chips where delamination of the resin sheet has occurred. D: There are 5 to 6 SAW chips where the resin sheet has peeled off. E: There are 7 or more SAW chips where the resin sheet has peeled off. Not usable.

[0084] The physical properties and evaluation results of each example and comparative example are shown in Tables 3 and 4 below. [Table 3] [Table 4]

[0085] Comparative Example 2, which did not contain the thermosetting resin (A), and Comparative Examples 1 and 2, which did not contain the polyfunctional maleimide compound (B) and the benzoxazine compound (C), showed inferior flexibility and adhesive strength compared to the other examples. This indicated problems with SAW chip protection and adhesion after thermal shock testing. In other words, it was found that achieving both excellent flexibility and low thermal expansion was difficult in these comparative examples.

[0086] On the other hand, the resin sheet containing thermoplastic resin (A), polyfunctional maleimide compound (B), benzoxazine compound (C), and epoxy resin (D) exhibited excellent SAW chip protection, and also showed good solder crack resistance and adhesion after thermal shock testing. Furthermore, the resin sheets shown in Examples 6-8 and 13-15 all received an A rating in all evaluation items, confirming their particularly excellent performance.

[0087] This disclosure is not limited to the embodiments described above, and may be modified as appropriate without departing from its spirit. Furthermore, this disclosure may be implemented by combining the embodiments described above or examples thereof as appropriate. [Explanation of Symbols]

[0088] 1, 11 circuit boards 2.12 Electronic Components 3 Hollow structure 4. Sealing layer (first sealing layer) 5. Second sealing layer 6, 13 Solder ball 10 Hollow Electronic Components 20 Test boards

Claims

1. A resin sheet for sealing hollow electronic components, for forming a sealing layer for hollow electronic components, The resin sheet is a resin composition comprising a thermosetting resin (A), a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D), and is a resin sheet for encapsulating hollow electronic components.

2. The resin sheet for sealing hollow electronic components according to claim 1, wherein the total content of a polyfunctional maleimide compound (B) having two or more maleimide groups, a benzoxazine compound (C), and an epoxy resin (D) in the resin composition is 5 to 180 parts by mass per 100 parts by mass of thermosetting resin (A).

3. The resin sheet for encapsulating hollow electronic components according to claim 1, wherein the resin composition further comprises an inorganic filler (E), and the inorganic filler (E) comprises silica particles.

4. The resin sheet for encapsulating hollow electronic components according to claim 3, wherein the content of the inorganic filler (E) in the resin composition is 5 to 70% by mass.

5. The resin sheet for sealing hollow electronic components according to claim 1, wherein the coefficient of linear expansion at 150 to 200°C of the cured product obtained by curing the resin sheet at 180°C for 2 hours is 3 to 750 ppm / K.

6. A resin sheet for sealing hollow electronic components according to claim 1, wherein the elongation at break at 100°C is 300 to 2000%.

7. The resin sheet for sealing hollow electronic components according to claim 1, wherein the resin sheet is bonded to a polyimide substrate and cured at 180°C for 2 hours, and the adhesive strength of the cured product at 25°C is 0.6 to 40 N / cm.

8. A hollow electronic component comprising a substrate, an electronic component mounted on the substrate, and a sealing layer that seals the electronic component while maintaining a hollow structure between the substrate and the electronic component, wherein the sealing layer is formed from a cured product of a resin sheet for sealing hollow electronic components as described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Hollow sealing resin sheet and method for manufacturing hollow package

    JP2014209568A